A hybrid SWOT-FANP model for energy policy making in Turkey. Issue 6 (2nd June 2016) - Kabak, Mehmet; Dağdeviren, Metin; Burmaoğlu, Serhat
ABSTRACT: Energy has a vital role in the development of countries. The situation of global increasing demand for energy, lack of domestic resources, energy prices, etc. forces the policymakers to plan energy policies in detail. In this paper, the strategic energy situation of Turkey is analyzed. This paper presents a hybrid model that combines strength, weakness, opportunity, and threat (SWOT) analysis with the fuzzy analytic network process (FANP) method. In the evaluation process, it is occasionally impossible to take precise information from decision makers (DMs) who can say their assessments relatively and approximately. It is also needed to use fuzzy logic to alleviate this problem. Since the evaluation and selection of alternative energy policies are complex multi-criteria decision making (MCDM) problem, one of the most popular MCDM methods, ANP, is used under fuzziness in this paper. For this aim, four factors and 21 sub-factors are determined and seven alternative policies are evaluated. It is computed that the most important three sub-factors are "major companies' interest for offshore drilling in Mediterranean and Black Sea, " "developing economy of the country, " and "rapidly increasing energy demand, " respectively. As a result, Turkish energy policy makers are advised to focus on the privatization of electric transmission and distribution facilities, integrating the national electric system with European transmission systems and turning the country into an energy hub and terminal to be able to get the rapid economic growth and mitigate future energy problems.